Ultrasound-Assisted sequential processing of barley straw using binary acidic and hydrated ternary deep eutectic solvents for nanocellulose production - Dileswar Pradhan; Swarna Jaiswal; Brijesh K. Tiwari; Amit K. Jaiswal (Ultrasonics Sonochemistry)
This study aimed to valorise barley straw by using a binary acidic deep eutectic solvent (DES) made from choline chloride and lactic acid for biomass pretreatment, and a hydrated ternary DES (HDES) composed of betaine, oxalic acid, and water (BOW HDES) for downstream processing to produce nanocellulose. The ultrasound-assisted DES pretreatment significantly enhanced lignin and hemicellulose solubilisation, achieving an average lignin removal of 70.54 % and hemicellulose solubilisation of 69.58 % under optimal conditions. Purification of US-DES-treated solid residue resulted in a cellulose yield of 39.81 ± 1.47 % with a purity of 91.31 ± 0.93 %, comparable to or exceeding conventional fractionation methods. The yield of lignin-rich material was 9.40 ± 0.89 % with a lignin purity of 83.29 ± 1.57 %. Further, nanocellulose was produced using a sequential process comprising low-viscosity HDES treatment, which improved fibre swelling and solubilisation, followed by high-intensity ultrasound (HIUS) treatment for nanoscale defibrillation. DLS analysis of the optimal nanocellulose sample revealed that 77.8 % of nanoparticles had a diameter below 100 nm, demonstrating a high yield of nanoscale material. XRD analysis confirmed the preservation of the cellulose I crystalline structure throughout processing, ensuring structural integrity. These findings demonstrate an efficient and sustainable biorefinery approach for lignin, cellulose, and nanocellulose extraction from agricultural residues, offering potential for scalable nanocellulose production.